2021
DOI: 10.1001/jamanetworkopen.2021.6147
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of Opioid Analgesics and Buprenorphine for Opioid Use Disorder During the COVID-19 Pandemic

Abstract: IMPORTANCEThe COVID-19 pandemic disrupted medical care, impacting prescribing of opioid analgesics and buprenorphine for opioid use disorder. Understanding these patterns can help address barriers to care. OBJECTIVE To evaluate how prescribing of opioid analgesics and buprenorphine for opioid use disorder changed throughout the COVID-19 pandemic among both new and existing patients. DESIGN, SETTING, AND PARTICIPANTSIn this cross-sectional study, use of opioid analgesics and buprenorphine for opioid use disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 8 publications
7
68
1
Order By: Relevance
“…The decrease may be explained by disruptions to outpatient and hospital clinical services and elective surgeries mandated during the early phase of the pandemic. Our results are consistent with a report indicating that existing patients maintained access to opioid medications, but the weekly number of opioid-naïve patients receiving opioid prescriptions decreased over March 18-May 19, 2020 ( Currie et al, 2021 ). A similar study reported plateauing of buprenorphine prescriptions ( Nguyen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease may be explained by disruptions to outpatient and hospital clinical services and elective surgeries mandated during the early phase of the pandemic. Our results are consistent with a report indicating that existing patients maintained access to opioid medications, but the weekly number of opioid-naïve patients receiving opioid prescriptions decreased over March 18-May 19, 2020 ( Currie et al, 2021 ). A similar study reported plateauing of buprenorphine prescriptions ( Nguyen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…The observed increase in benzodiazepine prescriptions in our study may be partly explained by the pivot toward telemedicine, which has been shown to be related to less attrition and improved depression symptoms in patients receiving teletherapy ( Mohr et al, 2008 ). Given the low rate of buprenorphine initiation during the pandemic ( Currie et al, 2021 ) and the prevalence of chronic pain in US adults (20.4% as of 2016, Dahlhamer et al, 2018 ), our finding of decreased opioid prescriptions following the emergency declaration suggests the need for further structural support in increasing telemedicine access among patients needing opioid prescriptions. Research on increasing and maintaining access to telemedicine across all patient needs including antidepressants, analgesics, and substance use disorder treatment remains crucial ( Di Carlo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…CHCs experienced enormous financial losses as a result of the pandemic, 26 some closing completely, creating uncertainty for patients receiving prescriptions and especially those at risk for opioid use disorders. 27 Our results can inform CHCs in their decision-making with regard to prioritizing patient outreach (eg, reaching out to their more medically complex patients) and providing access during this and future pandemics to mitigate high-risk opioid use.…”
Section: Discussionmentioning
confidence: 88%
“…The data revealed that while existing patients maintained access to buprenorphine treatment during the early months of the pandemic, the number of new patients receiving buprenorphine for opioid use disorder during the early months of the pandemic decreased by almost 25% and remained depressed through August 2020, even then only reaching 90% of projected levels. The study results imply that 36,954 fewer patients entered opioid use disorder treatment, which may have been associated with increases in overdose deaths ( Currie et al, 2021 ).…”
Section: Covid-19 and Opioid Morbidity And Mortalitymentioning
confidence: 93%
“…Most medication-assisted treatment (suboxone or methadone), support groups, and 12-step programs require in-person visits. Disruption to access for the usual in-person treatments may be associated with increase overdose deaths ( Currie et al, 2021 ).…”
Section: Covid-19 and Opioid Morbidity And Mortalitymentioning
confidence: 99%